Recalcitrant Warts Treated With Isotretinoin, an Old Drug in A New Role - Two Case Reports - Sharma, Dr. Rahul Kumar (International Journal of Innovative Research in Medical Science, 2017)
Warts are very common lesions encountered in dermatology practice. They are caused by human papillomavirus (HPV). We are presenting two cases of chronic recalcitrant warts treated successfully by Isotretinoin; one was having plantar warts and another had Condyloma acuminatum. The following case reports highlight its role as novel therapy in resistant widespread warts. Very limited literature is available on its role in the treatment of warts. The patients with warts especially genital warts suffer from great discomfort. As there is no fixed protocol or guideline to treat recalcitrant warts further studies are considered necessary.